Compósito de matriz cimentícia reforçados com fibras da capa do palmito pupunha - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2024)
The Paraná coastline is home to a large number of small producers of pupunha palm heart, and its municipalities have a low Human Development Index. Self-construction using cement pieces mixed with agricultural waste is one of the ways to combat poverty and reduce environmental impact. This study assesses the technical feasibility of cementitious composites with partial replacement of sand by lignocellulosic material from pupunha palm heart. Test specimens were prepared from cementitious composites filled with fibers from the outer layer of pupunha palm heart. The plant fibers were used in their natural state and treated with Tetraethyl Orthosilicate (TEOS). The fibers were ground and characterized for water absorption, FTIR, TGA, DSC, and their microstructure was analyzed using scanning electron microscopy (SEM). The treated fibers showed a decrease in water absorption, and microstructure analysis revealed that TEOS treatment resulted in silica deposition on the fiber's surface. Composites were prepared by replacing sand in mass proportions of Reference (0%), 1%, 1.5%, and 2% with plant fibers. Characterizations were performed in both fresh and hardened states. Consistency table test, water absorption, void content, capillarity, flexural tensile strength, and compression tests were conducted. With increasing substitution, the mortars experienced a loss of consistency, and a superplasticizer additive was used to standardize the spread. The Reference sample obtained the lowest absorption percentage and void index compared to the others, while samples with treated fibers showed lower absorption and void index values compared to samples with untreated fibers. In terms of strength tests, the reference mortar exhibited the best performance, followed by mortars with treated and untreated fibers. Despite the reduction in compressive and tensile strengths, it was observed that the specimens with fibers displayed a less brittle behavior before failure. With the exception of the samples with untreated fiber and sand replacement of 1.5% and 2%, all others exhibited compressive strength exceeding the minimum required by the standard. Samples that surpassed the minimum tensile strength requirement were associated with a 1% fiber replacement, both for treated and untreated fibers, in addition to those treated with 1.5%. These results are promising for the use of fibers in rural construction elements and components that do not require structural performance.
Keywords: Fibras Vegetais; Palmito Pupunha; Cimento Portland; TEOS; Vegetable Fibers; Pupunha Palm Heart; Portland Cement; TEOS; CNPQ::ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA